Producing Recombinant mTEX101; a Murine Testis Specific Protein - L Barzegar Yarmohammadi; MH Modarresi; S Talebi; R Hadavi; M Ostad Karampour; AR Mahmoudi; MM Akhondi; H Rabbani; M Jeddi-Tehrani (JRI, 2009)
Introduction: Production of antibodies against specific proteins of testis germ cells is of great significance for the investigation of processes involved in spermatogenesis, study of infertility problems and determination of the probable role of these proteins as cancer-testis antigens. Murine Testis Specific Recombinant Protein 101 (mTEX101) is a 38kDa, GPI-anchored protein which is expressed in testis germ cells of adult mice but it seems to be absent in other tissues. The structure and function of mTEX101 is not completely understood yet, but it is speculated that it may transduce biochemical signals into the cytoplasm since mTEX101 does not have an intracellular domain but the precise mechanisms are still ambiguous.Materials and Methods: RNA was extracted from three adult mice testis. The RNA was used in RT-PCR, employing a pair of specific primers for mTEX101 ORF region. TA-cloning technique was performed by the insertion of mTEX101 into a pGEM-T Easy Vector, followed by its subcloning into a His-tagged expression vector, pET-28a (+). The recombinant mTEX101 was then produced by transfection of the expression vector into BL 21 (DE3) E. coli strain.Results: A recombinant protein, weighing 27kDa, was produced upon IPTG-induction of the bacterial host. The presence of mTEX101 protein was detected through Western blot analysis by anti-mTEX101 peptide antibodies.Conclusion: We produced mTEX101 recombinant protein that could be used for the production of mono and polyclonal antibodies.
Keywords: Antibody production, Gametogenesis, Germ cells, Recombinant protein, Spermatogenesis, TES101 protein mouse, Testis, Glycoprotein